SETTLEMENT OF BREACH OF CONTRACT IN CREDIT AGREEMENTS WITH THIRD-PARTY VEHICLE COLLATERAL (BORGTOCHT VEHICLE) AT BPR SURASARI HUTAMA - Setya, Ferri; Moersidin, Murry Darmoko (jfpublisher, 2024)
This study examines the role of Rural Banks (BPR), particularly BPR Surasari Hutama, in managing non-performing loans secured by vehicle guarantees through non-litigation mechanisms. As financial institutions, BPRs are mandated to collect savings and distribute credit within the community, with each credit agreement (Akad Kredit) legally binding both parties through a written contract that includes a principal loan agreement and collateral provision. Employing a sociological-empirical research method, this study explores how legal norms are implemented in practice, especially in cases of credit default. BPR Surasari Hutama addresses such defaults primarily through familial mediation, emphasizing the protection of creditor and debtor rights outside formal judicial proceedings. This mediation process typically results in a written commitment from the debtor, which serves as the legal basis for the repossession of the collateral vehicle. The final step involves the debtor signing a Vehicle Handover Letter (SP3), authorizing the creditor to reclaim and sell the asset through mutual agreement. The findings indicate that this mediation-based approach, grounded in effective communication, enables efficient, court-free resolution of credit disputes. This model not only facilitates the enforcement of collateral agreements but also reinforces the importance of relational trust and cooperative negotiation in financial dispute settlement at the rural banking level.